2022
DOI: 10.1186/s13071-022-05168-z
|View full text |Cite
|
Sign up to set email alerts
|

Parasite dynamics in untreated horses through one calendar year

Abstract: Background Horses are host to a plethora of parasites. Knowledge of the seasonality of parasite egg shedding and transmission is important for constructing parasite control programs. However, studies describing these patterns are sparse, and have largely been conducted only in the United Kingdom. This study evaluated strongylid egg shedding patterns and transmission dynamics of Strongylus vulgaris in naturally infected and untreated mares and foals through one calendar year in Kentucky, USA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…At the whole blood transcriptome level, the pyrantel treatment per se contributed little to the variance in gene expression (2.92% on average, Figure S3 B) with no evidence of an inflammatory response, as previous data suggested. 70 However, anthelmintic treatment explained 20.2 and 17.3% of the variance in the host expression levels of neuroligin ( NLGN2 ) and solute carrier ( SLC10A7 ) coding gene, a transporter of various drugs 71 , 72 ( Figure S7 ), compatible with a direct effect of the pyrantel treatment on the host. A comparison between the treated and untreated low shedders 24h post-treatment found 13 differentially expressed (DE) genes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…At the whole blood transcriptome level, the pyrantel treatment per se contributed little to the variance in gene expression (2.92% on average, Figure S3 B) with no evidence of an inflammatory response, as previous data suggested. 70 However, anthelmintic treatment explained 20.2 and 17.3% of the variance in the host expression levels of neuroligin ( NLGN2 ) and solute carrier ( SLC10A7 ) coding gene, a transporter of various drugs 71 , 72 ( Figure S7 ), compatible with a direct effect of the pyrantel treatment on the host. A comparison between the treated and untreated low shedders 24h post-treatment found 13 differentially expressed (DE) genes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…A Swedish study confirmed the increased egg excretion in summer (Tydén et al 2019 ). The other British study detected no seasonality of strongyle egg shedding (Lester et al 2018 ; Steuer et al 2022 ). A recent study by Nielsen et al ( 2022 ) recommends that strongyles are best examined in spring or winter.…”
Section: Discussionmentioning
confidence: 89%
“…Equine strongylid egg shedding has been demonstrated to fluctuate by season in some studies (Poynter, 1954;Duncan, 1974;Wood et al, 2013;Nielsen et al, 2021), but not in others (Lester et al, 2018;Steuer et al, 2022). However, regardless of whether these fluctuations occur or not, the general recommendation is to focus egg count monitoring and anthelmintic treatments around the active parasite transmission season (ESCCAP, 2019;Nielsen et al, 2019) so that treatments are aimed at reducing pasture contamination.…”
Section: Introductionmentioning
confidence: 99%